The application of drama techniques to speaking tasks in Tieng Anh 6 to improve the students’ speaking performance - Trương, Quỳnh Anh (2020)
There is a large amount of drama techniques which empower the students to develop their speaking performance like hot- seating, role- play, improvisation, etc. In this study, I employ three popular drama techniques namely narration, role- play and hot- seating to improve the students’ speaking performance.